Morphological characterisation of diesel soot in oil and the associated extraction dependence - Key, Sarah; La Rocca, Antonino; Fay, Mike; Rance, Graham; Growney, David (2018)
The size and morphology of soot particles and agglomerates extracted from lubricating oil drawn from the sump of a diesel engine have been investigated and compared using Transmission Electron Microscopy (TEM) and Nanoparticle Tracking Analysis (NTA). Samples were prepared for electron microscopy imaging by both centrifugation and solvent extraction to investigate the impact of these procedures on the morphological characteristics, such as skeleton length and width and circularity, of the obtained soot. It was shown that centrifugation increases the extent of agglomeration within the sample, with 15% of the agglomerates above 200 nm compared to only 11% in the solvent extracted soot. It was also observed that the width of centrifugation extracted soot was typically 10 nm to 20 nm larger than that of solvent extracted soot, suggesting that centrifugation forces the individual agglomerate chains together. Moreover, centrifugation fails to extract a large percentage of particles below 50 nm, with only 4% of the agglomerates smaller than 50 nm in the centrifugation extracted soot, whereas agglomerates in this size range accounted for 19 % using solvent extraction. As TEM represents a comparatively time and cost expensive characterisation tool, unsuitable for high throughput testing required by industry, NTA was explored as a low cost, rapid alternative method for measuring particle size. It was found that results generated by NTA, within the limits of detection, correlated well with those obtained using TEM. This correlative electron microscopy and light scattering approach was further used to appraise the morphological characteristics of two commercial sources of carbon black (CB), enabling the selection of the most suitable soot surrogate, essential for the further development of oils with optimised functional properties.